KEANEKARAGAMAN TUMBUHAN FAMILI PANDANACEA DI KAWASAN HUTAN SIBAYAK II SUMATERA UTARA - Puspita, Ayu; Hutasuhut, Melfa Aisyah; Rahmadina, Rahmadina (Fakultas Biologi Universitas Jenderal Soedirman, 2024)
Pandanaceae includes Monocotyledoneae plants that have shrub, tree and liana habitus. This study aims to determine the types of members of the Pandanaceae family that live in the Sibayak II Forest Area in North Sumatra, as well as the diversity index and key identification of these members. The method used in this research is an exploratory survey method with a purposive sampling quadrat plot technique with 10 plots measuring 10m x 10m. The results obtained 6 species from the Pandanaceae family, namely Freycinetia javanica Blume, Freycinetia sumatrana Hemsl., Freycinetia sp., Pandanus furcatus Roxb., Pandanus houletti Carriere, Pandanus sp. The diversity index of the Pandanacaeae family is 2.504 which is classified as moderate. The identification key for the Pandanaceae family has common characteristics. The Pandanaceae family is found in highland tropical forests with high rainfall and reproduces vegetatively (budding) under favorable environmental conditions.